C-reactive protein binds to short phosphoglycan repeats of Leishmania secreted proteophosphoglycans and activates complement - Seow, Eu Shen; Doran, Eve C.; Schroeder, Jan-Hendrik; Rogers, Matthew E.; Raynes, John G. (Frontiers in Immunology, 2023)
Human C-reactive protein (CRP) binds to lipophosphoglycan (LPG), a virulence factor of Leishmania spp., through the repeating phosphodisaccharide region. We report here that both major components of promastigote secretory gel (PSG), the filamentous proteophosphoglycan (fPPG) and the secreted acid phosphatase (ScAP), are also ligands. CRP binding was mainly associated with the flagellar pocket when LPG deficient Leishmania mexicana parasites were examined by fluorescent microscopy, consistent with binding to secreted material. ScAP is a major ligand in purified fPPG from parasite culture as demonstrated by much reduced binding to a ScAP deficient mutant fPPG in plate binding assays and ligand blotting. Nevertheless, in sandfly derived PSG fPPG is a major component and the major CRP binding component. Previously we showed high avidity of CRP for LPG ligand required multiple disaccharide repeats. ScAP and fPPG only have short repeats but they retain high avidity for CRP revealed by surface plasmon resonance because they are found in multiple copies on the phosphoglycan. The fPPG from many species such as L. donovani and L. mexicana bound CRP strongly but L. tropica and L. amazonensis had low amounts of binding. The extent of side chain substitution of [-PO4-6Galβ1-4Manα1-] disaccharides correlates inversely with binding of CRP. The ligand for the CRP on different species all had similar binding avidity as the half maximal binding concentration was similar. Since the PSG is injected with the parasites into host blood pools and phosphoglycans (PG) are known to deplete complement, we showed that CRP makes a significant contribution to the activation of complement by PSG using serum from naive donors.